Flextime and Gen Z Work-Life Balance: The Moderating Roles of Job Crafting and Boundary Management - Abdul Kadir Alamudi; Maulidyah Amalina Rizqi (Universitas Negeri Semarang, 2026)
This research study examines the effectiveness of flextime policy on the Work-Life Balance (WLB) of Generation Z employees by evaluating the dual moderating roles of Job Crafting (an expansive strategy) and Boundary Management Strategies (a protective strategy). Flexible work arrangements (flextime) are often assumed to be the ideal solution for achieving Work-Life Balance (WLB). However, for Generation Z employees, this autonomy frequently triggers the